PRINCIPLES OF MANAGEMENT AND THE BHAGAVAD GITA - Chandekar, Shankar B. (Journal of Dharma, 2012)
Today, with the advent of globalization, liberalization and privatization, the world, indeed, has become a Monstrous Super Market. Business Managements are guided by the mechanistic view of life which encourages fierce competition and ‘survival of the fittest’. Managerial excellence is mostly centred round the final goal of creating "surplus" and fetching "maximum profit" for the owners who are at the top of the management. There is, however an awakening all over the world about the drawbacks of the Modern Art and Science of Management. A Holistic View of Management is gradually emerging; and a welcome shift in paradigm is on the horizon.